METHODOLOGY FOR IMPROVING TEACHING OF THE SUBJECTS OF "INFORMATION AND INFORMATION TECHNOLOGIES" ON THE BASE OF SOFTWARE TOOLS (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses the issues of creating multimedia presentations based on modern software tools and organizing lessons using them in the teaching of 5th grade "Informatics and Information Technologies" subjects in general secondary schools today.